1991
DOI: 10.1523/jneurosci.11-03-00881.1991
|View full text |Cite
|
Sign up to set email alerts
|

The temporal profile of 72-kDa heat-shock protein expression following global ischemia

Abstract: The potential role of the nonconstitutive 72-kDa heat-shock protein (HSP72) in selective neuronal vulnerability to ischemia was studied in rats subjected to graded global ischemia. Immunocytochemistry using a monoclonal antibody against HSP72 was performed on tissue collected after 24 hr of reperfusion. The appearance of HSP72 immunoreactivity correlated in a graded fashion with those regions known to be selectively vulnerable in ischemia. That is, HSP72 was induced in only hilar interneurons and CA1 pyramidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
49
1
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(61 citation statements)
references
References 28 publications
9
49
1
2
Order By: Relevance
“…This is consistent with previous HSP70 findings following global ischemia (Gonzalez et aI. , 1991;Simon et aL 1991) and hypoxia-ischemia (Ferriero et aI. , 1990).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous HSP70 findings following global ischemia (Gonzalez et aI. , 1991;Simon et aL 1991) and hypoxia-ischemia (Ferriero et aI. , 1990).…”
Section: Discussionsupporting
confidence: 93%
“…Vass et al (1989) in CA3, CA4, and dentate granule cell neurons known to survive, whereas HSP70 was minimally induced in CAl pyramidal neurons, which die. Sim ilarly, Simon et al (1991) found that short durations of global ischemia induced HSP70 in neurons that did not die, as assessed by acid fuchsin stains. Sharp et al (1991a) also found that MK-801, phen cyclidine, and ketamine induce HSP70 in cingulate gyrus neurons, which are known to survive.…”
Section: This Induction In the Endothelial Cells In Infarcted Brain Rmentioning
confidence: 94%
“…Indeed, the degree and duration of ischemia re quired to induce expression in brain remain poorly defined. In models of global ischemia, 2 min of isch emia was reported to trigger hippocampal expres sion of HSP-70 (Simon and Cho, 1990;Kirino et aI., 199 1;Nowak and Osborne, 199 1). Since ischemia for 2 min in normothermic gerbil brain is sufficient to deplete levels of ATP in most regions of hippo campus (Welsh et aI., 1990), it is apparent that even a brief period of energy failure is associated with increased expression of HSP-70.…”
Section: Discussionmentioning
confidence: 99%
“…These include mem bers of the heat shock and immediate early gene (IE G) families. Focal (Gonzalez et al, 1989;Li et al, 1992;Welsh et al, 1992;Kinouchi et al, 1993a,b) and global (Vass et al, 1988;Dwyer et al, 1989;Ferriero et al, 1990;Nowak et al, 1990;Gonzalez et al, 1991;Sharp et al, 1991 a;Simon et al, 1991;Blumenfeld et al, 1992) ischemia induces the hsp70 heat shock gene in brain. Though the pre cise role of hsp70 is unknown, it is believed to bind to denatured proteins (Anathan et al, 1986;Pel ham, 1986) and to protect the cell from subsequent injury (Pelham, 1986;Barbe et al, 1988;Lowen stein et al, 1991).…”
mentioning
confidence: 99%